2020
DOI: 10.1021/acs.jproteome.0c00518
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring to Search Engines: Bottom-Up Proteomics with Collision Energies Optimized for Identification Confidence

Abstract: Bottom-up proteomics relies on identification of peptides from tandem mass spectra, usually via matching against sequence databases. Confidence in a peptide−spectrum match can be characterized by a score value given by the database search engines, and it depends on the information content and the quality of the spectrum. The latter are influenced by experimental parameters, of which the collision energy is the most important one in the case of collision-induced dissociation. We examined how the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Since Byonic is a commercial software, we refrain from a detailed explanation of this phenomena. On the other hand, similar trend was found for unmodified tryptic peptides 24 earlier. The key reasons may include the difference in what types of fragment ions the engines look for and how they utilize experimental intensity information.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since Byonic is a commercial software, we refrain from a detailed explanation of this phenomena. On the other hand, similar trend was found for unmodified tryptic peptides 24 earlier. The key reasons may include the difference in what types of fragment ions the engines look for and how they utilize experimental intensity information.…”
Section: ■ Results and Discussionsupporting
confidence: 87%
“…22,23 For peptide identification, 28% NCE was found to be the optimal value on an Orbitrap mass spectrometer. 24 Confirmed sequence coverage of mAb peptides was also investigated, and a workflow using a step of two collision energies 6−10 eV apart was suggested. 22 For post-translationally modified peptides like N-or O-glycosylated ones, a stepped NCE value of 30−50% was found to be ideal by Cao et al, 25 but generally (30 ± 10)% is used by the community.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Given the differences in the peak picking and scoring algorithm of available search engines, 4 , 33 , 34 one may expect somewhat different experimental parameters to be optimal when different data evaluation procedures are used. This was indeed confirmed for unmodified peptides 35 but has not yet been explored for glycopeptides.…”
Section: Introductionmentioning
confidence: 78%
“…The latter were measured on the same instrument earlier in our group. 35 Since pGlyco is designed for glycopeptide identification only, no pGlyco analysis was carried out in this section. It was found that N-glycopeptides need ca.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation